Angebot 14 : Zeichnungen - Druckgrafik. - Galerie Lüpke, Frankfurt am Main (Frankfurt : Galerie Lüpke, 1989)
Arcangelo ; Aubertin, Bernard ; Barcelo, Miguel ; Baviera, Vincenzo ; Darboven, Hanne ; Friedmann, Gloria ; Gaul, Winfred ; Green, Alan ; Haypeter, Werner ; etc.
Angebot 14 : Zeichnungen - Druckgrafik, Galerie Lüpke, Frankfurt am Main, September 1989
boek